Stemodia diplohyptoides (Plantaginaceae, Gratiolae): a new diploid species from South America - Sosa, Maria de Las Mercedes (2014)
Stemodia diplohyptoides (Plantaginaceae), a new species from Gratiolae tribe is described and illustrated. This taxon is found in northeastern Argentina, at the edge of the Parana River that surrounds the north and center of Misiones province (Argentina). It is a diploid that has been traditionally treated under Stemodia hyptoides, which is here re-circumscribed to include only autopolyploid plants (tetraploid and hexaploid). The diploid specimens may be distinguished from the polyploid S. hyptoides by several morphological features such as shape, pubescence and margin of the leaves, corolla length and corolla tube pubescence. In addition, scanning electron microphotographs of seeds, chromosomes numbers, a distribution map and a key to distinguish the related species are also provided. On the basis of morphological, cytological and geographical data, some evolutionary considerations are inferred.